Evaluation of Student Learning Outcomes on Square Materials With Problem-Based Learning Model - Erpin Evendi; Nur Hardiani (IKIP Mataram, 2021)
Good knowledge construction is a guarantee of achieving better learning outcomes. In the context of our current study, the PBL model is implemented in the classroom and further evaluation of students' cognitive learning outcomes is carried out. Specifically, the purpose of this study is to evaluate student learning outcomes on square material in the application of the PBL model. This research is a quasi-experimental with pretest-posttest control group design. The number of research samples for each group was 25 students in a private Islamic school (equivalent to a secondary school) in Mataram, Indonesia. Data on student learning outcomes was collected using a learning outcome test instrument on square material. Descriptive and statistical analysis was carried out on student learning outcomes data, this was analyzed using the SPSS.23 tool. The results of the study show the advantages of the PBL model in improving student learning outcomes when compared to conventional learning. Finally, we recommend the use of this model in learning mathematics to improve student learning outcomes.